Adaptive chemistry lookup tables for combustion simulations using optimal B-spline interpolants. Issue 4 (4th July 2019) - Bode, Mathis; Collier, Nathan; Bisetti, Fabrizio; Pitsch, Heinz
Abstract : Flamelet models, which enable the storing of precomputed detailed chemistry into lookup tables, are widely used in combustion simulations. They allow the computation of accurate results at low computational cost, but standard implementations can lead to numerical problems due to a non-smooth representation, and their applicability is limited by memory requirements. Here, the methods used by a newly developed and optimised lookup table generator based on B-spline interpolation are presented. The creation of smooth representations of flamelet solutions requiring less than one fifth of the number of points in each direction compared to the non-smooth representations of standard lookup tables based on linear interpolation is shown to be possible. The new B-spline interpolation based tables are also applied within a large-eddy simulation of the Swirling Methane/Hydrogen Flame 1 and the results are compared to simulations using lookup tables based on linear interpolation or optimised artificial neural networks. Better performance of the B-spline interpolation based tables with respect to physical accuracy and numerical performance is demonstrated.